Perceived overall injustice and organizational deviance—Mediating effect of anger and moderating effect of moral disengagement - Qin, Ge; Zhang, Lihua (Frontiers in Psychology, 2022)
Introduction This study is dedicated to exploring the influence of perceived overall injustice on employee anger and deviant behavior. Based on fairness heuristic theory and cognitive appraisal theory of emotion, a model was developed to investigate the relationship between perceived overall injustice, anger and organizational deviance. Based on social cognitive theory, the moderating role of moral disengagement was proposed. Methods The data were collected from three Chinese manufacturing corporations with a total effective sample size of 264. SPSS 26 and Mplus 8.3 were adopted to analyze data. Confirmatory factor analysis, descriptive statistics analysis and correlation results were illustrated. Hierarchical regression was used to test the model. Results Statistical results showed that there is a significant positive relationship among perceived overall injustice, anger and organizational deviance. The moderating effect of moral disengagement on the relationship between perceived overall injustice and organizational deviance is significant, while that on the relationship between anger and organizational deviance is insignificant. Discussion This study built a model to discuss the emotional and behavioral influences of perceived overall injustice. The findings suggest that individuals feel more anger as the level of perceived overall injustice increases, which thus lead to higher level of organizational deviance. Morally disengaged employees are more likely to engage in organizational deviance after being treated unfairly. However, the moderating effect of moral disengagement on the relationship of anger and organizational deviance was insignificant. The reason might be because anger is an aggressive emotion and individual experiencing anger may lead to impulsive behavior regardless of moral rules. Implications and limitations have been discussed.